2021
DOI: 10.2196/26220
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Clinical and Precision Medicine Tumor Boards—Cloud-Based Platform–Mediated Implementation of Multidisciplinary Reviews Among Oncology Centers in the COVID-19 Era: Protocol for an Observational Study

Abstract: Background Multidisciplinary tumor boards play a pivotal role in the patient-centered clinical management and in the decision-making process to provide best evidence-based, diagnostic, and therapeutic care to patients with cancer. Among the barriers to achieve an efficient multidisciplinary tumor board, lack of time and geographical distance play a major role. Therefore, the elaboration of an efficient virtual multidisciplinary tumor board (VMTB) is a key point to successfully obtain an oncology te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
0
11
0
1
Order By: Relevance
“…This is in line with what is described in the literature. Indeed, the data-banking system and virtual meetings have been reported by Blasi et al 2021 to be time-saving [ 24 ]. In addition, the Care Manager, as a dedicated professional figure, assumes a key role in the collection of the documentation to be examined and analyzed during the multidisciplinary meeting, the data entry and reporting of patient’s clinical history.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with what is described in the literature. Indeed, the data-banking system and virtual meetings have been reported by Blasi et al 2021 to be time-saving [ 24 ]. In addition, the Care Manager, as a dedicated professional figure, assumes a key role in the collection of the documentation to be examined and analyzed during the multidisciplinary meeting, the data entry and reporting of patient’s clinical history.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising, since we do not expect that MTB impacts on cancer stage at the time of diagnosis (which is mostly influenced by primary prevention and screening), but rather on clinical decision making and, therefore, on clinical outcomes. Indeed, scientific evidence shows that promoting a digital aid for MTB strengthens the health professionals’ network and the multidisciplinary approach to the decision-making process to provide the best cancer care by improving patient management plans thanks to the combined knowledge of different specialists [ 24 ]. As regards clinical decision making, our study showed a significant increase in the percentage of patients undergoing radio-chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many articles highlight the need for scalable informatics tools to support MTBs ( 1 , 26 , 27 ). Another essential need is data security and data privacy, to be able to ensure anonymity and secure sensitive data ( 26 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many articles highlight the need for scalable informatics tools to support MTBs ( 1 , 26 , 27 ). Another essential need is data security and data privacy, to be able to ensure anonymity and secure sensitive data ( 26 , 28 ). The challenges of clinical interpretation of genetic variants based on manual investigation of extensive literature may also be served by automated solutions ( 1 , 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%